Do migrant remittances matter for financial development In Kenya? - Roseline Nyakerario Misati; Anne Kamau (Kenya Bankers Association (KBA), 2018)
The paper analyzes the relationship between remittances and financial development using the autoregressive distributed lag (ARDL) method based on Kenyan quarterly data from 2006 to 2016. Five different indicators of financial development are used in the study. The study used credit to the private sector, number of mobile transactions, value of mobile transactions, number of mobile agents and number of bank accounts. The results show a strong positive relationship between remittances and all the five indicators of financial development in the long run equations. The results imply that higher levels of remittances provide opportunities for opening bank accounts, enhancing savings and accessing financial systems for recipients besides exposing the unbanked to existing and new financial products. The results also confirm the potential advantage of embracing modern and advanced technology that facilitates international mobile transfer channels. Usage of international remittance transfer through mobile technology reduces costs by eliminating the need for physical branches and personnel to attend to walk-in customers that dominates traditional remittance business models besides offering remittance actors convenience and safety. There is therefore a policy window for the Government to leverage on remittances as a tool of financial inclusion and financial depth particularly through continued expansion of the regulatory space that accommodates wider usage of international mobile remittance transfer channels. Moreover, given the strong positive relationship between remittances and credit to the private sector and number of bank accounts, commercial banks and other players in the remittance market may also find it useful to develop customized products for migrants that can tap into their remittances. Financial intermediaries can for example consider providing better deposit interest rates to diaspora deposits compared to deposits in local currency and allowing usage of regular remittance flows as collateral for credit allocation among other incentives, to tap into the huge potential of money remitted by migrants to Kenya.
Keywords: 330; Rücküberweisungen; Finanzmarkt; Entwicklung; Kreditgeschäft; Elektronisches Geld; Finanzielle Inklusion; Kenia